(untitled) (Raparin Journal of Humanities (RJH), 2025)
Economic administrative regulation is regarded as the primary mechanism for overseeing economic activities, maintaining market equilibrium, and safeguarding the public interest. At this juncture, the administrative authority assumes the task of controlling economic activity through the regulation of prices, quality and the existence of competition. Meanwhile, in economic transactions, the consumer is often viewed as the vulnerable party, defined as an individual who acquires goods or services to fulfil personal, non-professional needs. Therefore, safeguarding this vulnerable group within economic transactions needs a robust legal framework, to achieve this, countries have grounded their national legislation on international treaties, regional agreements, and United Nations guidelines, in the Kurdistan Region, the inefficiency of the Consumers Protection Council is evident, despite its establishment under the Iraqi Consumers Protection Law No. 1 of 2010, which is applicable in the Kurdistan Region through Law No. 9 of 2010, this makes the law inadequate for consumers protection, due to the lack of balance with the rapid economic growth in the region, compounded by the inefficiency of central administrative authorities, by establishing a public policy, they will play a crucial role in overseeing markets and ensuring product safety, while local administrative authorities will be responsible for field monitoring and directly addressing consumer complaints, this makes the urgent need to activate economic administrative regulations in order to safeguard consumers and enhance confidence in the markets governed by the Kurdistan Regional Government. Beside that, administrative power suffers due to complicated issues, the most marked being one lack of cooperation the ambiguity in legal clauses regarding the systemization of responsibilities. these issues impose urgent action on the Kurdistan region to gather administrative institutions under one roof by working toward activating the Consumer Protection Council. Moreover, it is necessary to reorganize and clarify the responsibilities of administrative authority concerning consumer protection.